2012
DOI: 10.1186/1471-2334-12-299
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic influenza A/H1N1 virus infection and TNF, LTA, IL1B, IL6, IL8, and CCLpolymorphisms in Mexican population: a case–control study

Abstract: BackgroundSome patients have a greater response to viral infection than do others having a similar level of viral replication. Hypercytokinemia is the principal immunopathological mechanism that contributes to a severer clinical course in cases of influenza A/H1N1. The benefit produced, or damage caused, by these cytokines in severe disease is not known. The genes that code for these molecules are polymorphic and certain alleles have been associated with susceptibility to various diseases. The objective of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…In addition, the AT genotype at rs4073 in IL8 [16] and the AG at rs909253 in LTα, also known as TNF-β [16,26], were associated with the inflammatory response [13]. In the present study, the genotypes identified to play a role in IAV, were also rep- compared to those with "no-risk" genotype.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In addition, the AT genotype at rs4073 in IL8 [16] and the AG at rs909253 in LTα, also known as TNF-β [16,26], were associated with the inflammatory response [13]. In the present study, the genotypes identified to play a role in IAV, were also rep- compared to those with "no-risk" genotype.…”
Section: Discussionmentioning
confidence: 86%
“…One-way analysis of variance test showed a significant difference between these risk genotypes groups in the average levels of some nutritional factors such as licated to have similar effects in another study among a Greek population [27]. Such polymorphisms in hypercytokinemia genes are associated with an increased potential to synthesize cytokines and chemokines and influence the nature and effectivness of the inflammatory immune response [13,27]. Overall, risk alleles of IL8 and TNF-β were associated with a 1.5 to 3-fold increased risk of IAV infection and with a 1.2 to 2.4 increased risk of death [16,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations